PENGARUH PENDIDIKAN DAN PELATIHAN TERHADAP KINERJA PEGAWAI YANG DIMEDIASI OLEH KOMPETENSI: Studi Pada Pegawai Kecamatan Tlanakan Kabupaten Pamekasan - Chamariyah; Imam Puuji; C.Sri Hartati (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2022)
The objectives of this study are: 1) To examine and analyze the effect of education on employee performance in Tlanakan Subdistrict, Pamekasan Regency; 2) To test and analyze the effect of education on competence in Tlanakan Subdistrict, Pamekasan Regency; 3) To test and analyze the effect of competence on the performance of employees in Tlanakan Subdistrict, Pamekasan Regency; and 4) To examine and analyze the effect of education on the performance of the employees of the Tlanakan Subdistrict, Pamekasan Regency which is mediated by competence. The research method used is quantitative method, with a sample of 62 employees. Based on data analysis using PLS, the results showed that; 1) Education has a significant effect on employee performance, with the original sample value of 0.319; 2) Education has a significant effect on competence, with the original sample value of 0.545; 3) Competence has a significant effect on employee performance, with the original sample value of 0.338; and 4) Education has a significant effect on employee performance mediated by competence, with the original sample value of 0.184. The significance value of all research variables at = 0.05 with a 95% confidence level. The variable that has a significant dominant effect is education on competence.